Pengaruh Zakat Perbankan dan Corporate Social Responsibility Terhadap Kinerja (Studi Kasus pada PT. BPRS Puduarta Insani Tembung) Periode 2018-2022 - Lubis, Hana’ Salsabila; Rahma, Tri Inda Fadhila; Syahbudi, Muhammad (Regress: Journal of Economics & Management, 2023)
The objective of this study is to ascertain the impact of banking zakat and corporate social responsibility (CSR) on financial performance. The study employed a purposive sampling technique, specifically utilizing financial reports and annual zakat transactions data from PT. Puduarta Insani Tembung for the period of 2018-2022. The research employs many data analysis techniques, including descriptive statistical analysis, classical assumption test, multiple linear regression analysis, t test, f test, and coefficient of determination test. The findings from the multiple linear regression analysis indicate that partially zakat has a favorable, albeit statistically insignificant impact on financial success. On the other hand, corporate social responsibility (CSR) has a considerable influence on financial performance. The findings demonstrate that both zakat and corporate social responsibility (CSR) have a simultaneous impact on financial performance. The coefficient of determination test reveals that zakat and corporate social responsibility (CSR) have a 32.2% impact on financial performance.